Assessment of trend and etiological factors for cesarean delivery among women residing in Ahmedabad, Gujarat, India - Govani, Kapil J.; Jogia, Priyanka D. (International Journal of Research in Medical Sciences, 2017)
Background: Cesarean section (CS or C-section) is a surgical intervention and it is the 2nd commonest surgery performed on women in India after tubectomy operation. So, the study was conducted with objectives to assess the socio-demographic profile of recently delivered women and to assess the trend and etiological factors of cesarean delivery among women. Methods: A cross sectional study was conducted among recently delivered women of Ahmedabad city, Gujarat, India during April to September 2015. Pretested performa was used for study after informed consent. Total 200 women were selected for study. Results: Majority (56%) of women were belongs to 25 to 30 year. age group. Few (5%) of women were found illiterate. 31% women were delivered through cesarean section. Majority (63.5%) of women were delivered at Government hospitals. Most common reason (23%) for cesarean delivery was previous history of LSCS. Most preferred (33%) first choice of contraceptive method was barrier method. Conclusions: Commonest reasons for cesarean deliveries were previous history of LSCS, Oligohydramnios and prolonged labor. Most preferred first choice of contraceptive method was barrier method followed by Oral Contraceptive pills.